The last caldera-forming eruption in Kamchatka: Ksudach volcano, 1700-1800 14C-years ago - Braitseva O.A.; Melekestsev I.V.; Ponomareva V.V.; Kirianov V.Yu. (1995)
A catastrophic explosive eruption occurred 1700-1800 14C-years ago at Ksudach Volcano in Kamchatka. It was one of the AD greatest Plinian-type eruptions. It erupted 18-19 km3 of pyroclastic material and produced a collapse caldera 4 × 6.5 km in size and 6.5-7 km3 in volume. The eruptive column rose to a height of 23 km. It was the last caldera-forming eruption in the Kuril-Kamchatka region. It resembled an eruption that occurred at Krakatau in 1883 in type and size. The eruption was bound to have a climatic impact, impaired the Earth's ozone layer, and produced an acid peak in the Greenland ice sheet. -from Journal summary